2014
DOI: 10.12816/0003343
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Prevalence of Alcohol Consumption , Tobacco Use and Sexual Behaviour among Adolescents in Urban Areas of the Udupi District , Karnataka, India

Abstract: abstract:Objectives: The aim of this study was to assess the prevalence of alcohol consumption, tobacco use and risky sexual behaviour among adolescents, and to evaluate the socioeconomic factors potentially influencing these behaviours. Methods: This cross-sectional study was conducted from January to April 2011 among 376 adolescents (15-19 years old) studying in different schools and colleges in Udupi, India. The Youth Risk Behavior Survey questionnaire and guidelines were followed for data collection. Parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
30
2
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 14 publications
7
30
2
7
Order By: Relevance
“…8 Median age of initiation of alcoholism was 18years in the present study similar to a study in Udupi, Karnataka which found as 16.8years. 9 Least age of alcohol consumption in our study was 5years. Our study revealed 24.4 % of parents, 29.9 % of relatives and 46 % of friends were having substance abuse.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…8 Median age of initiation of alcoholism was 18years in the present study similar to a study in Udupi, Karnataka which found as 16.8years. 9 Least age of alcohol consumption in our study was 5years. Our study revealed 24.4 % of parents, 29.9 % of relatives and 46 % of friends were having substance abuse.…”
Section: Discussionmentioning
confidence: 65%
“…This is similar to the study in Udupi which showed males consumed more alcohol and tobacco and factors such as religion and tobacco use among family members were found to be influential. 9 A study among males in Thiruvananthapuram showed that religion and sociodemographic factors such as marital disharmony, poor income, poor education and unemployment are significantly associated with alcohol dependence. 5,6 …”
Section: Determinants Of Substance Abusementioning
confidence: 99%
“…25.92% used tobacco for stress relief, curiosity and peer pressure. 10 However Ramanan et al found in their study that 44.4% of respondents too alcohol for fun or desire to taste, thus showing that curiosity about alcohol is a strong reason for its consumption.…”
Section: Discussionmentioning
confidence: 90%
“…5 Here the risk behaviors are very much exacerbated in college going youth populace of South Chennai.…”
Section: Discussionmentioning
confidence: 99%